Microstructural investigation and hole quality evaluation in S2/FM94 glass-fibre composites under dry and cryogenic conditions. (April 2021) - Giasin, Khaled; Barouni, Antigoni; Dhakal, Hom Nath; Featherson, Carol; Redouane, Zitoune; Morkavuk, Sezer; Koklu, Ugur
S2/FM94 glass fibre reinforced epoxy is an aerospace-grade composite currently bonded with aluminium alloys and installed in parts of the Airbus A380 fuselage. In addition to its abrasive and hard nature, S2/FM94 glass fibre is sensitive to thermal effects developed during the drilling process, and therefore using coolants becomes necessary. However, conventional oil and water-based coolants are not suitable for drilling of composites. Cryogenic coolants on the other hand are an attractive choice for machining composites and are environmentally friendly. In this study, a new environmentally friendly cryogenic cooling technique in a liquid nitrogen bath was used for the drilling of S2/FM94 glass fibre reinforced epoxy composite. The aim was to investigate the effect of drilling parameters and cryogenic cooling on cutting forces, surface roughness, hardness and delamination factor at hole entry and exit sides. The workpiece was drilled within a cryogenic bath. In this way, both cryogenic workpiece cooling and tool cooling were obtained. In addition, the drill geometry is fixed and only the cutting parameters (i.e. spindle speed and the feed rate) are varied under dry and cryogenic conditions. The results indicate that the spindle speed and cryogenic cooling had the most significant influence on the cutting forces and surface roughness parameters (Ra and Rz ), while the use of cryogenic cooling had the most significant influence on increasing the hardness and size of delamination at entry and exit sides of the holes.